ROLE OF CLINICAL PHARMACIST IN ASSESSMENT OF DRUG RELATED PROBLEMS OF CARDIOVASCULAR AGENTS IN DEPARTMENT OF CARDIOLOGY IN A TERTIARY CARE HOSPITAL – A PROSPECTIVE OBSERVATIONAL STUDY - NAGA SUBRAHMANYAM S; TAGOORE VIJAYA LAKSHMI D; NAGA RAJU GV; PAVAN KUMAR GV (Innovare Journal Health Sciences, 2019)
In total of 173 prescriptions of the patient, the total number of 329 drug interactions (DIs) was found, in which the 240 interactions were found in male and 89 in the female bearing 72.90% and 27.10%, respectively. Patient was of various age groups, in which the maximum frequency was seen in the age group of 61–70 years having 105 interactions bearing the percentage of 31.9%. According to the participation of different age group of the male and female with their corresponding age. The participation of male is high having frequency of 240 (72.9%) than female participation of frequency 89 (27.1%). The participation of male in the age group of 61–70 years is 83 and the female is 40 in the age group of 51–60 years. Potential DIs (PDIs) were categorized based on the gender. In that compared to 13 (40.6) females, males 19 (59.4%) were found to have more PDIs. Our study is more PDIs in adult patients. Because in adults lacking of nutrition’s and in elderly patients multiple prescribers, multiple drugs and multiple diseases. The number of potential drug-DI (PDDI) increased with an increase in the number of drugs prescribed. The numbers of drug prescribed increase with age. This DI has a potential to increase or decrease the therapeutic effect or to increase the risk of adverse drug reaction. An increased awareness of PDDIs, rational coprescription of drugs, and a close monitoring of patients in whom these drugs are prescribed are recommended. The recommendation is based on the special monitoring and the perspiration of the clinical pharmacist. The DI observed in the geriatric patient is more severe and common in compared to the other groups of study. The geriatric patient is physiological disability in correspond with the first-pass metabolism and the presence of the other diseases which also enables the multiple prescriptions causing polypharmacy. The gender specification also the cause of the interaction, the female is more prone to the DI due to the hormonal distribution in the body and inability of the physiological function to absorb and the distribution. The special training should be provided to the pharmacist for looking forward of the geriatric patient and female patient. The training regarding the prescription their adherence, use, toxicity, and dosage regimen is being properly enabled in the training for the practical application. This study helps to know the different interaction related to the cardiovascular agent with own class of the drug and the other class of drugs used therapeutically to care the disease.